Ventilation and air conditioning for school buildings - Štefanič, Pavol; Straková, Zuzana (CLIMA 2022 conference, 2022)
One of the basic problems of school buildings is the unsatisfactory thermal insulation properties of peripheral building structures. Unsatisfactory, especially in terms of the creation and long-term maintenance of microclimatic conditions in the classroom, is the complete absence of mechanical ventilation systems. In almost all schools, ventilation is based on the natural exchange of air through windows. Such a solution is no longer satisfactory today. In the old school buildings, the old ventilation shafts were usually abolished and in the new schools, there are no such shafts at all. In general, in many places, it is also forbidden to open windows during breaks for safety reasons. In addition, the method of window ventilation is based only on the subjective feelings of teachers and students; and since the human factor is unable to determine sufficient air quality with the help of its organs, the result is that the interior is not sufficiently ventilated. This also results in an unacceptable concentration of CO2 in the classroom, a high level of resistance, an increasing level of relative humidity, and dust content in the indoor air. This is an unacceptable situation for teachers 'and students' health. The quality of the indoor environment of school buildings directly impacts the ability to concentrate and the attention of teachers and students. In this article, we will take a closer look at 6-week experimental measurements of the indoor microclimate in kindergarten. The measurement took place in two rooms, a playroom and a bedroom, where there were 22 children plus 1 or 2 adults at the same time. The measurement results for some quantities are acceptable, but in particular, the concentration of carbon dioxide is unacceptable.